The abundance and isotopic composition of Cd in iron meteorites. (14th December 2013) - Kruijer, Thomas S.; Sprung, Peter; Kleine, Thorsten; Leya, Ingo; Wieler, Rainer
Abstract Cadmium is a highly volatile element and its abundance in meteorites may help better understand volatility‐controlled processes in the solar nebula and on meteorite parent bodies. The large thermal neutron capture cross section of 113Cd suggests that Cd isotopes might be well suited to quantify neutron fluences in extraterrestrial materials. The aims of this study were (1) to evaluate the range and magnitude of Cd concentrations in magmatic iron meteorites, and (2) to assess the potential of Cd isotopes as a neutron dosimeter for iron meteorites. Our new Cd concentration data determined by isotope dilution demonstrate that Cd concentrations in iron meteorites are significantly lower than in some previous studies. In contrast to large systematic variations in the concentration of moderately volatile elements like Ga and Ge, there is neither systematic variation in Cd concentration amongst troilites, nor amongst metal phases of different iron meteorite groups. Instead, Cd is strongly depleted in all iron meteorite groups, implying that the parent bodies accreted well above the condensation temperature of Cd (i.e., ≈650 K) and thus incorporated only minimal amounts of highly volatile elements. No Cd isotope anomalies were found, whereas Pt and W isotope anomalies for the same iron meteorite samples indicate a significant fluence of epithermal and higher energetic neutrons. This observation demonstrates that owing to the high Fe concentrations in iron meteorites, neutron capture mainly occurs at epithermal and higher energies. The combined Cd‐Pt‐W isotope results from this study thus demonstrate that the relative magnitude of neutron capture‐induced isotope anomalies is strongly affected by the chemical composition of the irradiated material. The resulting low fluence of thermal neutrons in iron meteorites and their very low Cd concentrations make Cd isotopes unsuitable as a neutron dosimeter for iron meteorites.